Role of storage on quality, nutritional and biochemical properties of garlic bulbs grown depending on different fertilizer applications - Turfan, Nezahat; Kibar, Beyhan; Kibar, Hakan (Springer Science and Business Media LLC, 2023)
This study was carried out to determine the effects of fertilizer applications (control, inorganic fertilizer and barnyard manure + humic acid + inorganic fertilizer), storage temperatures (2, 10 and 20 °C) and durations (30, 60 and 90 days) on post-harvest quality, nutritional and biochemical properties of garlic bulbs during storage. As storage temperature and storage duration increased, weight loss and respiration rate also considerably increased. A significant effect of different fertilizer applications on weight loss, respiration rate and biochemical properties of garlic bulbs was not observed. Highly significant positive correlations were observed between pH and weight loss, b* and Chroma, L* and Hue angle, Ag and Sn, Ag and Cd, Mn and K, Sn and Cd, K and P. In conclusion, storage at 2 °C may be recommended as the best treatment to maintain post-harvest quality and to prolong storage life of garlics. Among fertilizer applications, inorganic fertilizer came to the forefront in terms of post-harvest quality. When the storage durations are examined, it was determined that garlic bulbs can be stored for up to 90 days without losing its quality much. The results of the present study will provide potential knowledge about post-harvest storage of garlic bulbs for further investigations. © 2023, The Author(s) under exclusive licence to Society for Plant Research.
Keywords: Allium sativum L; Fertilization; Temperature; Storage period; Quality